PERANCANGAN PUSAT WISATA KULINER NUSANTARA DENGAN PENDEKATAN ARSITEKTUR TRADISIONAL SUNDA DI KOTA SERANG - Luthfi Ali Hanafiah; Anggraeni Dyah; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
The Nusantara Culinary Tourism Center is a building that functions as a central container that serves Indonesian dishes from various islands from Sumatra to Papua. So that visitors are expected to feel a different feel from the usual restaurant by enjoying various types of Indonesian food, which is supported by various recreational facilities. By applying the concept of Sundanese Traditional Architecture, is expected to be able to help preserve traditional buildings owned by Indonesia, including this Sundanese traditional building, especially in the Serang City area, Banten which is one of the areas with the majority of the Sundanese tribe and also makes this design one of the newest tourism icons with a traditional feel.